Antibacterial Activity and Preliminary Phytochemical Screening of Four Medicinal Plants - Sirag, Nizar; Ahmed, Elhadi M M; Mohammed, Anwar; Abubakr, Mohamed (Gezira Journal of Engineering and Applied Sciences, 2018)
The present study was undertaken to investigate the antibacterial activity and to find the biologically active functional groups of four medicinal plants. The ethanolic extracts which were obtained by maceration were tested against in vitro five bacterial strains, using cup-plate agar diffusion method. Preliminary phytochemical screening techniques were also used to test for the presence and nature of the active constituents in these plant extracts.      Extracts of the plants; Adansonia digitata , Eucalyptus globulus and Trigonella foenum graecum showed a remarkable antibacterial activity against all tested bacterial strains. Meanwhile, the ethanolic extract of Ficus sycomorous exhibited a considerable antibacterial activity against Proteus mirabilis , Pseudomonas aeuroginosa and Staphylococcus aureus. The preliminary phytochemical screening revealed the presence of terpenes, tannins and saponins in all tested plant extracts, whereas alkaloids and cardiac glycosides were found in appreciable amounts in extracts Trigonella foenum graecum and Adansonia digitata respectively.       It can be concluded that the tested plants demonstrating broad spectra of activity which may help to discover new chemical classes of antibiotics that could serve as selective agents for the maintenance of health.